Ketersediaan dan Pola Spasial Ruang Terbuka Hijau Publik di Kota Pangkalpinang - Rizka Liddiyawatie; Edi Rusdiyanto; Sodikin Sodikin (BRILIANT: Jurnal Riset dan Konseptual, 2026)
The availability of public green open spaces (RTH) plays an important role in maintaining ecological balance and urban environmental quality. In the city of Pangkalpinang, rapid growth in built-up areas has created challenges in terms of the ideal proportion and distribution of RTH. This study aims to analyze the level of availability and spatial distribution patterns of public green open spaces to assess the suitability and equity of their functions in the city. The approach used is quantitative descriptive with the support of spatial analysis based on geographic information systems (GIS) to map the distribution and calculate the ratio of public green open spaces to the area. The results of the study show that the total area of public green space in Pangkalpinnang City has not reached the minimum standard of 20% of the city area, and its distribution tends to be clustered, especially in subdistricts with high population density. This condition indicates an imbalance in access to green space and has implications for a decline in environmental carrying capacity.